A 24-hour Approach to the Study of Health Behaviors: Temporal Relationships Between Waking Health Behaviors and Sleep. Issue 2 (17th September 2013) - Irish, Leah A.; Kline, Christopher E.; Rothenberger, Scott D.; Krafty, Robert T.; Buysse, Daniel J.; Kravitz, Howard M.; Bromberger, Joyce T.; Zheng, Huiyong; Hall, Martica H.
Abstract: Background: Although sleep is often associated with waking health behaviors (WHB) such as alcohol consumption, caffeine use, smoking, and exercise, the causal direction of these relationships is unclear. Purpose: The present study used time series data to examine the temporal dynamics of WHB and sleep characteristics in participants of the Study of Women's Health Across the Nation Sleep Study. Methods: Three hundred three women completed daily assessments of WHB and wore wrist actigraphs to measure sleep characteristics for the duration of the study (mean = 29.42 days, SD = 6.71). Results: Vector autoregressive modeling revealed that weekly patterns of sleep and WHB best predicted subsequent sleep and WHB suggesting that the associations between WHB and sleep persist beyond their immediate influence. Some WHB predicted some subsequent sleep characteristics, but sleep did not predict subsequent WHB. Conclusions: These novel findings provide insight into the temporal dynamics of 24-h behaviors and encourage consideration of both sleep and WHB in health promotion and behavior change efforts.